Study on the stability of iron tailings dam improved by curing agent - Li, Shujian; Wang, Guangjin; Wang, Menglai; Du, Xidong; Zhao, Bing; You, Jun; Zhu, Yuanting; Pu, Zhanglong; Pang, Jiantao; Lan, Rong; Liu, Mingsheng (Frontiers in Earth Science, 2025)
Fine-grained tailings exhibit poor permeability, prolonged consolidation time, low mechanical strength, and difficulty in dissipating excess pore water pressure. Tailings disposal often encounters challenges such as dam construction difficulties, inadequate seepage drainage from the dam body, gentle slopes on sedimentation areas, and poor stability. Starting from the basic physical properties of fine-grained tailings and taking a tailings pond in Sichuan Province as the engineering background, The curing test was carried out on the mixed tailings when the proportion of fine-grained tailings was 60%, and the optimal proportion of cementitious materials was studied when the mixed tailings were solidified for 28 days under the proportion of fine-grained tailings. Under the optimal proportion of cementitious materials, the mixed tailings when the proportion of fine-grained tailings was 60% were solidified to improve their strength, and the stability of the modified mixed tailings dam was explored. So as to provide reference for the utilization of fine tailings.